Pharmacological and Non-Pharmacological Management of Obstructive Sleep Apnea: Life Sciences- Dentistry - Gorripati, Jahnavi Purna; Godbole, Surekha Dubey (International Journal of Life Science and Pharma Research, 2023)
Obstructive sleep apnea (O.S.A.), also referred to as obstructive sleep hypopnea – is a sleep disorder that involvescessation or significant decrease in airflow in the presence of breathing effort. It is the most common type of sleep-disorderedbreathing. It is characterized by episodes of total or partial airway collapse and decreased oxygen saturation or sleep arousal. Asa result of this disturbance, sleep is interrupted and non-restorative. It significantly raises morbidity and mortality in both developedand developing countries. This review aims to review relevant studies on obstructive sleep apnea. The method used is acomputerized search method, the pathophysiology, clinical presentation, complications, diagnostic procedures, and therapeuticchoices from the literature. The effects of O.S.A. on cardiovascular health, mental disease, quality of life, and driving safety aresevere. This course of action highlights the interprofessional team's involvement in treating obstructive sleep apnea, itspathophysiology, and its causes.